2002
DOI: 10.1084/jem.20011930
|View full text |Cite
|
Sign up to set email alerts
|

CD8α2 CD11b+ Dendritic Cells Present Exogenous Virus-like Particles to CD8+ T Cells and Subsequently Express CD8α and CD205 Molecules

Abstract: Recombinant porcine parvovirus virus-like particles (PPV-VLPs) are particulate exogenous antigens that induce a strong, specific cytotoxic T lymphocyte (CTL) response in the absence of adjuvant. In the present report, we demonstrate in vivo that dendritic cells (DCs) present PPV-VLPs to CD8+ T cells after intracellular processing. PPV-VLPs are captured by DCs with a high efficacy, which results in the delivery of these exogenous antigens to 50% of the whole spleen DC population. In vivo, a few hours after inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 57 publications
5
89
0
Order By: Relevance
“…Martinez del Hoyo et al reported that splenic CD8a -DC differentiate into CD8a + DC in vivo [30], although another recent study presented conflicting results [31]. Moreover, several recent studies indicate that the surface expression level of CD11b on CD8a + and CD8a -DC subsets changes during maturation or after Ag uptake, at least in the spleen [32,33]. In this study, we could not determine whether DC underwent phenotypic change after OVA uptake, because we isolated DC at a single time point after OVA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez del Hoyo et al reported that splenic CD8a -DC differentiate into CD8a + DC in vivo [30], although another recent study presented conflicting results [31]. Moreover, several recent studies indicate that the surface expression level of CD11b on CD8a + and CD8a -DC subsets changes during maturation or after Ag uptake, at least in the spleen [32,33]. In this study, we could not determine whether DC underwent phenotypic change after OVA uptake, because we isolated DC at a single time point after OVA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally the expression of CD8␣ was used to mark DCs thought to be of lymphoid origin (1,34), it is now clear that this surface Ag is expressed on a variety of quite different DC subsets. We were interested in two particular subsets expressing CD8 that have been implicated in either CTL priming (12,13,35) or antiviral immunity (5,14). The first is the conventional CD8 DC subset identified by Vremec et al (1) and which has recently been shown to be important in cross-presentation of Ag for both CTL priming and tolerance (12,29).…”
Section: Resultsmentioning
confidence: 99%
“…These DCs have been shown to preferentially cross-present model cell-associated Ags to prime CD8 ϩ T cell responses, consistent with the notion that they play a key role in generating antiviral immunity (12). However, while this subset has been shown to preferentially present class I-restricted Ag derived from nonreplicating virus-like particles (13), there is currently no comparable data involving an infectious live virus. In addition, other DC subsets have been implicated in other aspects of antiviral immunity.…”
mentioning
confidence: 87%
“…Indeed, an lymphocytic choriomeningitis virus infection has been shown to change the predominant DC subset from pDC to mDC to divert host immune response away from anti-viral immunity [24]. On the other hand, it was reported that pDC accumulate in the spleen after infection with murine cytomegalovirus [25], and that mDC present exogenous virus-like particles to CD8 T cells and subsequently become CD8 + [26].…”
Section: Introductionmentioning
confidence: 99%